Emerging applications of nanoparticles and architectural nanostructures : current prospects and future trends - Barhoum, Ahmed; Makhlouf, Abdel Salam Hamdy (Micro & nano technologies., 2018)
Emerging Applications of Nanoparticles and Architecture Nanostructures: Current Prospects and Future Trends discusses the most important current applications of nanoparticles and architecture nanostructures in a comprehensive, detailed manner. The book covers major applications of nanoparticles and architecture nanostructures, taking into account their unusual shapes and high surface areas. In particular, coverage is given to applications in aerospace, automotive, batteries, sensors, smart textile design, energy conversion, color imaging, printing, computer chips, medical implants, pharmacy, cosmetics, and more. In addition, the book discusses the future of research in these areas. This is a valuable reference for both materials scientists, chemical and mechanical engineers working both in R & D and academia who want to learn more on how nanoparticles and nanomaterials are commercially applied.